Analisis Kegiatan Ekstrakurikuler Pramuka dan Nilai Gotong Royong Siswa SD Pacar Keling I Surabaya - Devi Hardianti; Badruli Martati; Kunti Dian Ayu Afiani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Character building currently requires a continuous process. Character will be a very important component for a student to build a good generation. It means that the character of students is very important to determine a person's attitude and behavior. Forming character in adult students is rather difficult to realize good character, so it will be better to form children's character from an early age. For this, it is necessary to develop the potential of students who aim at character education through extracurricular programs which are activities outside of learning hours. This extracurricular program is an additional activity whose allocations outside the learning hours are not stipulated in the 2013 curriculum. The Scout Movement is one of the places and efforts to foster the character of the easy generation by using scouting education to be implemented according to the interests of the development of elementary school students. Scout extracurricular activities will apply the value of cooperation that will be instilled in students. When the extra scouting activities take place students will discuss with other students in a team which will form a group at the scout level. The purpose of this article is to instill the formation of national character values ​​in students more effectively through scout extracurricular activities by emphasizing the value of cooperation and solidarity. Mutual cooperation can change behavior, ways of thinking and how to act to make students better and integrated